Differentiation drives the erosion of positivity on social media - Hongkai Mao; Yuan Chang Leong; Yutong Jiang; Alex Koch; William J. Brady; Joshua Conrad Jackson (Proceedings of the National Academy of Sciences, 2026)
Most people believe that social media discourse is negative and divisive. Here we show how this negativity can evolve even when users are not motivated to be negative. We propose that social media users seek to differentiate themselves from other users, and it is easier to differentiate oneself through negativity than positivity because negative information is more heterogeneous and counternormative than positive information. This makes users increasingly likely to post negative comments as a conversation unfolds and it becomes more challenging to make unique contributions. Analyzing 2.05 billion comments from 2,150 Reddit communities shows that comments become more negative over time, both within threads and community histories. This trend toward negativity is mediated by the semantic uniqueness of comments, suggesting that it arises from users differentiating themselves. This trend is strongest when initial dialogue is positive, making negative comments highly counternormative. We replicate these patterns in an experiment simulating social media dialogue ( n = 3,685). Participants become more negative over time, but only when incentivized to be unique, and especially when dialogue begins positively. These findings suggest that the structure of social media platforms interacts with human motivation to foster a drift toward negativity over time in online discourse.